Process variables optimization for synthesizing novel calcium-based metal-organic frameworks for feasible synthetic estrogen adsorption - Sukatis, Fahren Fazzer; Jori Roslan, Muhammad Qusyairi; Looi, Ley Juen; Lim, Hongngee; Abdul Rahman, Mohd Basyaruddin; Aris, Ahmad Zaharin (Elsevier, 2024)
Calcium-based Metal-Organic Frameworks (Ca-MOFs) hold great promise for environmental remediation due to their non-toxic nature, eco-friendliness, and cost-effectiveness. However, ensuring the structural integrity of MOFs after water exposure is crucial for industrial applications. This study investigates the physicochemical properties and structural stability of Ca-MOFs as potential adsorbents for water purification. The synthesis temperature, time, and reactant ratio significantly influence Ca-MIX's surface area and yield. The ideal conditions for synthesizing Ca-MIX, achieving a surface area of 20.45 m2/g and a yield of 18.56 kg/m³ per day, were achieved at a temperature of 120 °C, a reaction time of 16 h, and a metal-to-linker molar ratio of 1:0.33:0.33, respectively. The efficacy of a calcium-based MOF with a mixed linker, Ca-benzenedi and tricarboxylate (Ca-MIX) was explored, for removing the hazardous endocrine disrupting such EE2 from water. Ca-MIX exhibits high adsorption capacity at 97.17 μg/g and rapid 1-h adsorption. The adsorption process using the pseudo-second-order and Langmuir models were analysed, both describing it well. Notably, Ca-MIX efficiently removes EDCs like EE2, even at trace concentrations. Thus, Ca-MIX emerge as promising sorbents for adsorption-based removal of EDCs from polluted water.